Employee strategic goal sight and strategic action: the moderating role of openness to experience - Feng Hu; Xiao Jie Lu; Zeng qing Wei; Juan Peng; Shichang Liang; Zhi xuan Gao (Frontiers in Psychology)
IntroductionScholars have examined various factors influencing employee actions, such as goal congruence, personality traits, and job fit. However, they have overlooked employees’ strategic goal sight. This paper investigates how employees strategic goal sight affects their strategic actions and explores the moderating influence of their openness to experience.MethodsA questionnaire survey of 908 employees from various companies was conducted, and data analysis was performed using AMOS and SPSS.Results(1) Employee strategic goal sight significantly influences employee strategic actions positively; (2) Perceived insider status acts as a mediator between employee strategic goal sight and employee strategic actions; and (3) Openness to experience moderates this effect, as evidenced by: With increasing levels of employees openness to experience, the positive impact of their strategic goal sight on perceived insider status and strategic actions gradually diminishes.DiscussionThese findings not only enhance understanding of the relationship between employees’ strategic goal sight and strategy but also offer significant implications for guiding employees to engage in strategic behaviors that foster the company’s strategic development.